PENERAPAN TEKNIK BERMAIN MERONCE DALAM MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK DI TAMAN KANAK-KANAK PERTIWI DESA SEMAYA - Rachman, Sry Anita; Mujtahidin, Samsul; Sasakawati, Herni (JURNAL ASIMILASI PENDIDIKAN, 2023)
This research aims to determine the form and method of playing ronce activities to improve fine motor skills in young children. This type of research uses classroom action research with a qualitative approach. Data collection methods are observation and documentation. The data analysis technique used in this research is descriptive qualitative. The result of this research is a meronce activity consisting of beads and pieces of straw with implementation using preparatory stages, namely preparing tools and materials, conditioning the children before the activity begins, agreeing on play activities; application, namely the child takes the beads with his right hand using two fingers and inserts the string into the hole of the bead and tightens it; closing, namely tidying up their activity tools, asking about feelings during the activity. The results of this activity can be seen that the development of meronce activities improves children's fine motor skills in Pertiwi Kindergarten, Semaya Village and meronce activities can be used as a stimulation tool in developing children's fine motor skills.